The Deep Learning Revolution: Transforming Indonesia's Education System Towards the Digital Era 2025: Revolusi Pembelajaran Mendalam: Transformasi Sistem Pendidikan Indonesia Menuju Era Digital 2025 - Nabila Hilyatunisa (Journal of Educational Research and Learning Analytics, 2025)
This study analyzes the deep learning revolution in transforming Indonesia's education system toward the digital era 2025. Through a systematic literature review using Scopus database covering 2015-2025, this research identifies semantic ambiguity surrounding "deep learning" which refers to pedagogical dimensions (meaningful, mindful, and joyful learning) and technological dimensions (AI-powered deep learning). Findings reveal that synergizing both concepts can accelerate the achievement of Merdeka Belajar policy objectives through learning personalization, adaptive assessment, and enhanced educational accessibility. However, implementation faces critical barriers including digital infrastructure gaps, low teacher digital literacy, and absence of comprehensive policy frameworks. The study recommends an integrated strategic framework encompassing national AI-education roadmap formulation, equitable infrastructure investment, continuous educator capacity development, and multi-stakeholder collaboration to realize effective and inclusive educational transformation.